Plan de actividades motrices y su incidencia en el desarrollo del equilibrio en los niños y niñas de 6 – 8 años de la escuela básica profesor Carlos Coello Icaza, del cantón Vinces, Provincia de Los Ríos, año 2023 - Mora Chevez, Carlos Antonio (2023)
Physical education has been considered as a fundamental discipline for motor development and the integral formation of the child, especially when it is implemented from childhood because it affects the evolution of the social, affective, cognitive and motor spheres. As a result of this evolution, basic and specialized motor skills are consigned, which are determinant in the daily life of the child; however, something very common is the deficiency shown in terms of balance ability from an early age, which affects the child's performance in other learning areas in the future. The purpose of this research was to analyze the incidence of a plan of motor activities in the development of balance in boys and girls aged 6 - 8 years from the Professor Carlos Coello Icaza Basic School, in Vinces Canton, Los Ríos Province, through a mixed research approach, descriptive-correlational and with a pre-experimental design of longitudinal cut. A group of students (40 in total) and 1 teacher were selected to whom the data collection instruments were applied: interview and checklist. A plan of motor activities facilitates the development process of the cognitive, motor and socio-affective spheres; in this case, it will specifically enhance the levels of balance in boys and girls between 6 and 8 years of age. In this sense, it is known that they support a formulation of systematized, graduated and pertinent activities, to comply with those goals that arise within the teaching-learning process.